Outcomes of European Basic Laparoscopic Urological Skills (EBLUS) Examinations: Results from European School of Urology (ESU) and EAU Section of Uro-Technology (ESUT) over 6 Years (2013-2018) - Somani, Bhaskar K; Van Cleynenbreugel, Ben; Gözen, Ali-Serdar; Skolarikos, Andreas; Wagner, Christian; Beatty, John; Barmoshe, Sas; Gaya Sopena, Jose Maria; Kalogeropoulos, Theodoros; Faba, Oscar Rodriguez; Salas, Rafael Sanchez; Schmidt, Marek; et al. (European urology focus, 2020)
BACKGROUND: The European School of Urology (ESU) and EAU Section of Uro-Technology (ESUT) started hands-on-training (HOT) sessions in 2007 along with structured European Basic Laparoscopic Urological Skills (EBLUS) examinations in 2013. EBLUS includes an online theoretical course, HOT by expert tutors on a set of dry-lab exercises, and finally a standardised examination for skill assessment and certification. OBJECTIVE: To analyse the results and predictors of success from the EBLUS examinations that were conducted during the European Urology Residents Education Programme (EUREP) and other international and national dedicated ESU events. DESIGN, SETTING, AND PARTICIPANTS: ESU has been delivering EBLUS courses and examinations over the past 6 yr (2013-2018) in more than 40 countries worldwide. Trainees were asked about their laparoscopic background (procedures assisted/performed) and about the availability of HOT or simulator/box trainer in their facility. Apart from the online theoretical course, 4 HOT tasks [(1) peg transfer, (2) pattern cutting, (3) single knot tying, and (4) clip and cut] with its quality assessment of depth perception, bimanual dexterity, and efficiency were a part of the assessment and were considered critical to pass the EBLUS examination. RESULTS AND LIMITATIONS: A total of 875 EBLUS examinations were delivered (EUREP, n=385; other ESU events, n=490), with complete data available for 533 (61%) participants among which 295 (55%) passed the examinations. Pass rate increased on a yearly basis from 35% to 70% (p<0.001) and was similar between EUREP (56%) and other ESU/ESUT events (55%). The significant predictors of success were passing tasks 1 [odds ratio (OR): 869.9, 95% confidence interval (CI): 89.6-8449.0, p<0.001] and 2 (OR: 3045.0, 95% CI: 99.2-93 516.2, p<0.001) of the examinations. A limitation of EBLUS was its inability to provide more advanced training such as wet-lab or cadaveric training. CONCLUSIONS: Over the past few years more trainees have passed the European Basic Laparoscopic Urological Skills (EBLUS) examinations. Trainees who spend more time on laparoscopic procedures demonstrated a better performance and pass rate. We found almost no difference between the EBLUS results collected from EUREP and other ESU/ESUT events, which confirms the robustness of the training and examinations conducted worldwide. PATIENT SUMMARY: Training in laparoscopy helps trainees pass the European Basic Laparoscopic Urological Skills (EBLUS) examinations, reflected by an increase in the pass rate over the past 6 yr. Our results also confirm the robustness of EBLUS training and examinations worldwide.
Keywords: Endourology; klinické kompetence; Schools, Medical; EUREP; biomedicínské technologie; Europe; Time Factors; Evropa; Laparoscopy; školy lékařské; urologie; Educational Measurement; Clinical Competence; Training; výuka - hodnocení; ESU; Urologic Surgical Procedures; Humans; ESUT; Simulation; Urology; Biomedical Technology; časové faktory; EAU; urologické chirurgické výkony; laparoskopie; EBLUS; lidé